Ahmad is sending a message to Hadi - Lai, Adrian (New Straits Times, 2015)
The contest for the Pas presidency next month, the first in five decades, was a clear signal there was growing dissent against Datuk Seri Abdul Hadi Awang's leadership, political an analysts said.